HUBUNGAN PENGETAHUAN DENGAN TINGKAT KONTROL PENYAKIT ASMA DI POLI PARU RS. TK. III DR. REKSODIWIRYO PADANG - Clara Nadia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Asthma in Indonesia has increased cases from the year 2016 (1,256 cases) to the year 2017 (2,148 cases). The number of asthma patients in pulmonary polyclinic RS.TK.III dr. Reksodiwiryo Padang Hospital as many as 515 peoples in 2018, in 2019 found as much as 521 people with an average asthma patient who visited 35 peoples for a week. This research aims to know the relationship between knowledge with the level of asthma control in the pulmonary clinic of TK. III Dr. Reksodiwiryo Padang Hospital. This research is descriptive analytic with cross sectional study approach conducted in Juni until October 2021. The population in this study were all asthma patients who came to pulmonary polyclinic as much as 35 peoples. Data collection tools in the from of questionnaires and processed by computerized using chi-square. The results of the study were obtained largely (80%) Patients with asthma control levels are not controlled and more than half (57,1%) Patients with less good knowledge. There is a link between knowledge with the degree of asthma control in pulmonary polyclinic in TK. III Dr. Reksodiwiryo Padang Hospital with the value P (0.027). through the head of TK. III Dr. Reksodiwiryo Padang Hospital to nurses in pulmonary clinic to further enhance health promotion or health counseling efforts to improve the knowledge of patients in asthma controllers.